2019
DOI: 10.1002/jsfa.9547
|View full text |Cite
|
Sign up to set email alerts
|

Mixed‐cropping systems of different rice cultivars have grain yield and quality advantages over mono‐cropping systems

Abstract: BACKGROUND A mixed‐cropping system that enhances farmland biodiversity has the potential to improve grain yield and quality; however, the impacts of growing different rice cultivars simultaneously has been rarely investigated. In the present study, five popular rice cultivars were selected and ten mixture combinations were made according to the growth period, plant height, grain yield and quality, and pest and disease resistance. Seedlings of the five cultivars and ten mixture combinations (mixed‐sowing of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…There were 11,100 rice cultivars released by the country (1641) and provinces (9459) from 2000 to 2019 [ 29 , 30 ], during which agronomic traits and resistance to biotic and abiotic stresses were improved to ensure higher yield potentials. Both the TRP and GPA were significantly correlated with the number of annually released new rice cultivars ( Table 3 ), indicating that the rise of rice production in China is also contributed by the release of new rice cultivars [ 31 , 32 ]. The R coefficient was largest in MRP, suggesting that middle rice production benefited most from the released new rice cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…There were 11,100 rice cultivars released by the country (1641) and provinces (9459) from 2000 to 2019 [ 29 , 30 ], during which agronomic traits and resistance to biotic and abiotic stresses were improved to ensure higher yield potentials. Both the TRP and GPA were significantly correlated with the number of annually released new rice cultivars ( Table 3 ), indicating that the rise of rice production in China is also contributed by the release of new rice cultivars [ 31 , 32 ]. The R coefficient was largest in MRP, suggesting that middle rice production benefited most from the released new rice cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence analysis demonstrates that intercropping studies generally focus on four aspects as indicated by keywords of intercropping/maize, biodiversity/conservation, agroforestry, and carbon, respectively. Given that applications of synthetic fertilizers significantly increased grain yield over the past decades, but overuse of chemical fertilizer leads to soil and environmental pollution and threatens agricultural sustainability [77], more studies are required to develop efficient approaches so as to improve the crop quality while maintaining or increasing yield to meet food security and higher demands of food quality [78][79][80]. As intercropping has been well studied in well-developed countries including the USA and the mostly populated countries including India and China, more intercropping studies in undeveloped countries in Africa should be conducted to fight starvation and malnutrition and to adapt to climate change [63,81].…”
Section: Discussionmentioning
confidence: 99%
“…reported a mixed‐cropping system produced higher yields than a mono‐cropping in the same area. Li et al 18 . found that mixed cropping using different rice varieties improved grain yield and quality more than mono‐cropping systems did.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we measured the agronomic characteristics of rice varieties planted in mixed cropping, and those rice varieties were mono‐cropped separately as control. Rice in the mixed‐cropping system displayed relatively high leaf photosynthetic rates, total aboveground biomass levels, and grain appearance quality scores 18 9,29,30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation